The Relationship between the Characteristics of Influencers and Tiktok Social Media Content to the Brand Image of Cimory Yogurt Squeeze Products (Survey on Tiktok Content Commentators @Cheekykiddo) - Heriyanti Heriyanti; Lulu Ummarzhan Chania (Budapest International Research and Critics University, 2022)
A variety of beneficial advancements made possible by the use of digital technology can be fully taken advantage of, particularly in the usage of influencers. 100 samples of @cheekykiddo material comments from TikTok were utilized in this study to examine the effects of influencer types and TikTok social media content on the perception of the Cimory Yogurt Squeeze product brand. The quantitative analysis strategy in this work uses a multiple linear regression analysis methodology. The study's findings demonstrate a strong correlation between the TikTok social media content and the influencer criteria. These findings are evident from the statistical test results, which show a strong correlation between the brand image of the Cimory Yogurt Squeeze product, which is promoted and advertised through the TikTok social media account @cheekykiddo, and the influencer criteria and TikTok social media content. With the correct influencers chosen, research recommendations to address the phenomena of using TikTok social media to develop a brand image on a brand are very powerful in helping the audience accept the message that the business wants to deliver. In order to effectively promote a message or product, influencers need to use and maximize social media. While viewers who are aware of the shared video content can pick and rate the appropriate material so that the advertisements can be believed.